Interaction of self-assembled squalenoyl gemcitabine nanoparticles with phospholipid-cholesterol monolayers mimicking a biomembrane - Ambike, Anshuman (Langmuir : the ACS journal of surfaces and colloids, 2011)
© 2011 American Chemical Society